Influence of Th(NO3)4, KCl and pH on the Reduction of HgCl2 Under X- and UV-Radiations. - PRASHAD, JAGDISH; RANJANA SURI., (MISS) (Asian Journal of Chemistry, 2010)
The yield of Hg2Cl2 is maximum at relatively high pH, diminished progressively with decrease of pH and is completely inhibited beyond a critical pH. In the presence of Th(NO3)4, slight reduction is observed. The results are explicable by assuming the existence of hydrated molecular ion H2+ (hydr.).